Literature Analysis on the Implementation of Digital Media Maharah Qira’ah Based on Text To Speech / Analisis Literatur tentang Implementasi Media Digital Maharah Qira’ah Berbasis Text To Speech - Nevy Agustina; Koderi Koderi; Guntur Cahaya Kusuma; Erlina Erlina; Ahmad Bukhori Muslim (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
This article aims to analyze the literature related to the implementation of Text-to-Speech (TTS) technology in the teaching of maharah qira’ah (reading skills) in Arabic language education. The method used is a literature review by analyzing selected scholarly sources published between 2019 and 2024. The findings indicate that TTS technology contributes positively to enhancing students’ phonetic comprehension, pronunciation, and learning motivation. It also promotes self-directed and inclusive learning, especially for students with special needs. Nevertheless, several challenges remain, such as suboptimal TTS voice quality for Arabic, semantic context mismatches, and limited integration into the curriculum. Analysis using the VOS viewer application shows that this topic holds further development potential in the academic realm. Therefore, further research is needed to develop TTS systems that are more adaptive to the complexity of the Arabic language, along with implementation strategies aligned with pedagogical needs. This article offers insight into the urgency of integrating technology into Arabic language learning and highlights the potential of TTS as an innovative tool to improve students’ reading competence.Abstrak: Artikel ini bertujuan untuk menganalisis literatur terkait implementasi teknologi TTS dalam pembelajaran maharah qira’ah. Metode yang digunakan adalah literature review dengan menganalisis sumber-sumber ilmiah terpilih dari tahun 2019 hingga 2024. Hasil kajian menunjukkan bahwa TTS memberikan kontribusi positif dalam meningkatkan pemahaman fonetik, pelafalan, dan motivasi belajar siswa. Teknologi ini juga mendorong pembelajaran mandiri dan inklusif, terutama bagi peserta didik dengan kebutuhan khusus. Meskipun demikian, beberapa kendala masih ditemukan, seperti kualitas suara TTS yang belum optimal untuk bahasa Arab, ketidaksesuaian konteks semantik, dan keterbatasan integrasi dalam kurikulum. Analisis melalui aplikasi VOSviewer menunjukkan bahwa topik ini memiliki potensi pengembangan lebih lanjut dalam dunia akademik. Dengan demikian, dibutuhkan penelitian lanjutan untuk mengembangkan TTS yang lebih adaptif terhadap kompleksitas bahasa Arab serta strategi implementasi yang selaras dengan kebutuhan pedagogis. Artikel ini memberikan wawasan tentang urgensi integrasi teknologi dalam pembelajaran bahasa Arab dan potensi TTS sebagai alat bantu yang inovatif dalam meningkatkan kompetensi membaca peserta didik.